Answer: 1.02
Step-by-step explanation:
The graph g(x) is the graph of f(x) translated (5,2,3) units (down,up,left,right) , and g(x) =(f(x-3),f(x)-5,f(x)+3,f(x-2),f(x)+
marusya05 [52]
Answer:
The graph g(x) is the graph of f(x) translated <u>2</u> units <u>right</u>, and g(x) = <u>f(x-2)</u>
Step-by-step explanation:
g(x) passes through points (0, -5) and (1, -2), then the slope of g(x) is the same as the slope of f(x), which is 3.
f(x) passes through (0, 1) and g(x) passes through (2, 1). Therefore, the graph g(x) is the graph of f(x) translated 2 units right.
f(x - c) translates f(x) c units to the right, therefore g(x) = f(x-2)
In order to check this result, we make:
f(x) = 3x + 1
f(x-2) = 3(x-2) + 1
f(x-2) = 3x - 6 + 1
f(x-2) = 3x - 5 = g(x)
Answer:
12
Step-by-step explanation:
1-make the demonitores the same
2-remove digits next to (x)
3-solve manually
Step-by-step explanation:
use microsoft maths